+0  
 
0
227
1
avatar+2766 

The quadratic \(-6x^2+36x+216\)  can be written in the form a(x+b)^2+c, where a,b , and c  are constants. What is a+b+c?

tertre  Mar 12, 2017
 #1
avatar+12566 
+5

re-arrange    -6x^2 + 36x =-216       Divide by -6  (we'll multiply by -6 shortly to even things out)

                        x^2 -6x =  36          'complete the square'

                        x^2 - 6x + 9 = 36+9

                        (x-3)^2 -45    now multiply by -6

 

                        -6(x-3)^2 + 270       a = -6   b = -3  c = 270

 

                    a+b+c = 261

ElectricPavlov  Mar 12, 2017
edited by ElectricPavlov  Mar 12, 2017

18 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.